Pengaruh Beban Pajak Penghasilan Terhadap Manajemen Laba pada Perusahaan Sektor Perdagangan, Jasa dan Investasi Periode 2010-2015 yang Terdaftar di Bursa Efek Indonesia dengan Firm Size dan Leverage sebagai Variabel Kontrol. - Feliana Pramitasari; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to examines the affect of income tax expense of the previous year on earnings management activities of the current year of trade, service and investment public companies in Indonesia by using firm size and leverage as control variables. Furthermore, this study will used 58 financial reports of trade, service, and investment public company that registered in Indonesia Stock Exchange from 2010 until 2015. Modified Jones model was be used to calculate Discretionary Accrual which became a proxy of earnings management. The data tested by using multiple linear regression analysis.The results showed that income tax expense, firm size and leverage had affected on earnings management simultaneously. Income tax expense had negative affect on earnings management, on the other hand firm size had no affect on earings management. The variabel leverage had positive affect on earnings management.